DEVELOPMENT OF APPLICATION FOR MANAGING JOBS AND DOCUMENTATION RELATING TO OCCUPATIONAL HEALTH AND SAFETY IN A TOYS COMPANY - Azwir, Hery Hamdi; Dewi Puspa Kartikasari, Gusti Ayu (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2020)
PT. X has two procedures to control and monitor every work that is carried out inside the company area. One of them is Work Permit or known as Permit to Work (PTW). As identified during its direct observation in a quantitative approach by flow process chart and document flow chart, there are several problems in the system. The existing system has also been identified as running ineffectively. Management of PT X approved application development for the system as the problem solution. By following the guidance of SDLC phases, two customized applications were developed using visual basic for application. At last, a further observation was carried out following their implementation to the system. The final result of this research shows that the applications are successfully improving the system.